2023
DOI: 10.3390/app13126990
|View full text |Cite
|
Sign up to set email alerts
|

A Non-Destructive Measurement of Trunk Moisture Content in Living Trees Based on Multi-Sensory Data Fusion

Abstract: Water plays an important role in various physiological activities of living trees. Measuring trunk moisture content (MC) in real-time without damage has important guiding significance for transpiration research in forest ecosystems. However, existing standing tree MC detection methods are either too cumbersome to install or cause different degrees of damage. Here, we propose a novel Internet of Things (IoT) monitoring system that includes wireless acoustic emission sensor nodes (WASNs) and underground soil MC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…This is because water has a lower density compared to the wood fibers themselves. Therefore, as the moisture content of the wood decreases, its density increases [16,41].…”
Section: Physical and Anatomical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because water has a lower density compared to the wood fibers themselves. Therefore, as the moisture content of the wood decreases, its density increases [16,41].…”
Section: Physical and Anatomical Propertiesmentioning
confidence: 99%
“…Some studies revealed the existence of electrical properties potentials in trees that could be related to physiological processes in trees [15,16]. The tree electrical properties approach is also used to determine the quality of trees for sawlogs and breeding programs [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have revealed the existence of electrical property potentials in trees that could be related to their physiological processes [12,13]. The tree electrical property approach is also used to determine the quality of trees for saw logs and breeding programs [14,15].…”
Section: Introductionmentioning
confidence: 99%